Can Openly Accessible E- Theses Be Published as Monographs? A Short Survey of Academic Publishers. Issue 1 (26th April 2019) - Gilliam, Christian; Daoutis, Christine
ABSTRACT: Recent developments in scholarly communication call for revisiting the effect open access e-theses (OAETs) have on future publishing opportunities. We investigated 23 university and commercial presses—with a focus on the arts, humanities, and social sciences—with regard to attitudes toward accepting OAETs for publication as monographs. The findings suggest that manuscripts that are revisions of OAETs are always welcome for submission or considered on a case-by-case basis by 47.8% of university presses, with a further 48.5% expressing a willingness to publish on the basis of substantial content revision.